Nepal: Public vs. Private? - Nikku, Bala Raju (International Higher Education, 2013)
As one of the poorest countries in the world, Nepal (with 30 million people) is going through a series of transitions and is rewriting its constitution. Access to education and now to higher education is limited in Nepal.